Chlorido(2-formyl-6-hydroxyphenyl-κC (1))mercury(II) - Xu, Chen (International Union of Crystallography, 2009)
In the planar [r.m.s. deviation 0.0265 Å] title compound, [Hg(C(7)H(5)O(2))Cl], the Hg(II) atom shows a typical linear coordination by a C atom of a benzene ring and a Cl atom. The benzene C atom and the aldehyde O atom chelate the Hg(II) atom by assuming the Hg⋯O separation of 2.817 (9) Å as a weak intramolecular coordination bonding distance. The resulting five-membered metallacycle is nearly coplanar with the benzene ring dihedral angle 2.9 (1)°]. Intermolecular O—H⋯O hydrogen bonds are present in the crystal structure, resulting in a one-dimensional supramolecular architecture parallel to [201].